2014
DOI: 10.1093/bja/aet337
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system penetration of oxycodone after intravenous and epidural administration

Abstract: EudraCT reference number: 2011-000125-76.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(94 citation statements)
references
References 21 publications
4
87
2
Order By: Relevance
“…In the present study, CSF oxycodone levels in the EPI group were approximately 100‐fold higher than in the IV group. However, the observed peak concentrations in the present study were approximately one‐quarter of those in our previous study . The most likely explanation for this is that, in the present study, CSF samples were collected at the L4–5 level by a single puncture, whereas in the previous study a spinal catheter was used for CSF sampling, with the tip higher in the subarachnoid space.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, CSF oxycodone levels in the EPI group were approximately 100‐fold higher than in the IV group. However, the observed peak concentrations in the present study were approximately one‐quarter of those in our previous study . The most likely explanation for this is that, in the present study, CSF samples were collected at the L4–5 level by a single puncture, whereas in the previous study a spinal catheter was used for CSF sampling, with the tip higher in the subarachnoid space.…”
Section: Discussionmentioning
confidence: 99%
“…Epidural administration of oxycodone has been evaluated in few previous clinical trials . In the study by Bäcklund et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal experiments also showed that the κ receptor [7,8,9] is related to the relief of visceral pain. Therefore, the control of oxycodone on postoperative recovery period of acute pain in visceral pain may be better after laparoscopic resection of rectal tumor [10,11] . 2.…”
Section: Discussionmentioning
confidence: 99%